Identification of risk factors associated with occupational fatigue among employees at PT. XYZ - Anggraini, Tri Lidya; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
This study aimed to identify factors associated with fatigue among employees of PT. XYZ in Medan, a futures brokerage firm where preliminary observations indicated a high prevalence of exhaustion and decreased alertness among employees. This study aimed to identify factors associated with fatigue. A descriptive analytic study with a cross-sectional design was conducted using a total population sample of 45 employees. Data were collected on workload (measured as %CVL), work duration, work environment (assessed through a questionnaire), and occupational fatigue (measured using the IFRC questionnaire). Univariate, bivariate (Chi-square), and multivariate statistical analyses were performed. The results showed that 33.3% of participants experienced fatigue. Bivariate analysis demonstrated statistically significant associations between fatigue and workload (p=0.015), work duration (p=0.001), and work environment (p=0.006). Multivariate analysis further quantified these relationships, identifying the work environment as the most dominant risk factor (OR=3.18), followed by work duration (OR=2.4) and heavy workload (OR=2.4). In conclusion, an unsafe work environment, long work duration, and heavy workload are significant and quantifiable risk factors for occupational fatigue, with the work environment serving as the strongest predictor.